Pelaksanaan Program Pendidikan Kecakapan Hidup (Life Skill Education) dalam Upaya Meningkatkan Kesuksesan Siswa di MA Al-Badri Gumuksari Kalisat Jember - Musthofa (LP3M Universitas Islam Zainul Hasan Genggong, 2015)
High school graduates are expected to continue to the college. However, if they do not take the further education, so they will be expected to work. The expectations of schools and parents on the fresh graduates are that they can continue to university or be an independent after graduation. Based on the observation in this study, it is showed that 60% of the high school graduates can not proceed to university. Therefore, for those who are not able to proceed to the universities, it is hoped that they can support themselves by getting the job. Here is the importance of giving them the life skills education program (life skills education) and entrepreneurial subjects. To illustrate the problem, this study attempts to explore the data with a qualitative approach. In line with this approach, this kind of research is classified as a case study in the term of life skills education and entrepreneurial subjects. The purpose of this study was to describe: (1) the program planning of life skills education in MA-Albadri Gumuksari Kalisat Jember, (2) the educational program skills in MA-Albadri Gumuksari Kalisat Jember, (3) the discussion of subjects of entrepreneurship programs, (4) the description of students’ career success after completing a program of life skills education and acquire entrepreneurial subjects in the MA-Albadri Gumuksari Kalisat Jember. Moreover, based on the results, it is showed that: (1) the education planning programs of local advantages (life skills education) in MA-Albadri Gumuksari Kalisat Jember Foundation described the establishment of coordination within the parents, communities, committee, employers, and related agencies in the Jember regency; (2) the local advantages of education programs (life skills education) in MA - Albadri Gumuksari Kalisat Jember is realized by the establishment of the Institute. Furthermore, the quality and skills development (LPMK) are conducted outside the school hours (as an extracurricular activities) 4 hours each day and it is divided into 2 turns. The program is done creatively, which is carried out with equipment based on the predefined modules; (3) the application of entrepreneurial subjects in the MA-Albadri Gumuksari Kalisat Jember integrated into the curriculum of local excellence. MA is one of the applying school subjects of entrepreneurship, and the entrepreneurial learning process are held for 2 hours of lessons in each week; (4) the description of students career success after completing life skills education program (Life Skills Education) and acquire entrepreneurial subjects in MA-Albadri Gumuksari Kalisat Jember are indicated by the number of graduates who are able to run their own business, or work at another person’s place of business. The percentage of those who open a business or work is higher than those who go on to college (40%).